Detection of Plasmodium DNA in Saliva of ICT Positive Malaria Patients - Asma Farid, Fatima Saadat, Marina, Asia, Shahid Waseem, Wali Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
Malaria is one of the most common and dangerous tropical infections. WHO estimates 3 million people in 24 countries are at risk for malaria. Malaria eradication is a top global health priority. Mosquitos spread Malaria, WNV, and Dengue Fever. A female Anopheles mosquito bite transmits malaria. Night and dawn are peak times. Plasmodium falciparum, malaria, vivax, ovale, and knowlesi infect humans. The deadliest parasite is Plasmodium falciparum. Objective: To compare the sensitivity and specificity of blood and salivary PCR among malaria patients and assess saliva as a Malaria diagnostic medium. Methods: A cross-sectional survey was conducted from March 2020 to May 2020 at Rafah Hospital Islamabad. After approval from the ethical review board, 100 subjects were approached from patients admitted to the medical /pediatrics ward, diagnosed with malaria by ICT or Microscopy. After Informed consent, ICT malaria was again performed on all of these subjects; each subject had taken paired blood and saliva samples. Data were analyzed by using SPSS version 23 Results: The present study analyzed the prevalence of malarial DNA in the saliva of malaria- diagnosed patients and evaluated the efficiency of the saliva of malarial patients as an alternate medium for its diagnosis. Among 100 study participants, Blood PCR showed 100% Sensitivity and 51.9% specificity compared to salivary PCR among 100 study Participants. Moreover, Salivary PCR showed a Sensitivity of 65.8% and a Specificity of 27% compared to Blood PCR. Practical implication: This study will provide data about the comparison of sensitivity and specificity of blood and salivary PCR among malaria patients and assess saliva as a Malaria diagnostic medium. Conclusion: Our study concluded that Blood PCR has good sensitivity and specificity compared to saliva PCR keeping ICT as the Gold standard. Moreover, saliva can not be used as an effective medium for the Diagnosis of Malaria. Keywords: Malarial DNA, Saliva, Blood PCR, salivary PCR.